2023
DOI: 10.1155/2023/9810733
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-Derived IL-6 Potentially Drives Ferroptosis Resistance in B Cells in Lupus Kidney

Abstract: Ferroptosis resistance is vital for B cell development, especially in inflammatory diseases, yet the underlying mechanism is still unclear. In this study, based on the scRNA-seq technique and flow cytometry, we discovered a proportion of neutrophils exhibited upregulated expression of the IL-6 and correlated with the expression of IL-6 receptor and SLC7A11 from B cells in lupus kidney. Moreover, we identified that in lupus kidney, neutrophils could provide IL-6 to facilitate ferroptosis resistance in B cells v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…Intriguingly, the enhanced nuclear translocation of CaM-KIV in SLE patients fosters CREMα phosphorylation, further contributing to T-cell dysfunction in the disease. [71] Wang et al [72] further revealed that in the context of lupus nephritis, neutrophils secrete IL-6, aiding B cells in resisting ferroptosis by elevating SLC7A11 expression. Notably, both lupus patients and animal models display signs of B-cell ferroptosis.…”
Section: Slementioning
confidence: 99%
“…Intriguingly, the enhanced nuclear translocation of CaM-KIV in SLE patients fosters CREMα phosphorylation, further contributing to T-cell dysfunction in the disease. [71] Wang et al [72] further revealed that in the context of lupus nephritis, neutrophils secrete IL-6, aiding B cells in resisting ferroptosis by elevating SLC7A11 expression. Notably, both lupus patients and animal models display signs of B-cell ferroptosis.…”
Section: Slementioning
confidence: 99%